2010
DOI: 10.1370/afm.1161
|View full text |Cite
|
Sign up to set email alerts
|

Participatory Decision Making, Patient Activation, Medication Adherence, and Intermediate Clinical Outcomes in Type 2 Diabetes: A STARNet Study

Abstract: PURPOSE Participatory decision making (PDM) is associated with improved diabetes control. We examine a causal model linking PDM to improved clinical outcomes that included patient activation and medication adherence. METHODSThis observational study was conducted in 5 family physician offi ces. Diabetic patients were recruited by mail and by completing a study interest card at the conclusion of their offi ce visit. Two survey questionnaires, administered 12 months apart, elicited patients' ratings of their phys… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

8
173
0
8

Year Published

2011
2011
2022
2022

Publication Types

Select...
10

Relationship

0
10

Authors

Journals

citations
Cited by 221 publications
(189 citation statements)
references
References 38 publications
8
173
0
8
Order By: Relevance
“…For example, there is evidence from cross-sectional studies that provider behaviors can support patient activation. Patients who report that their provider helped them in very concrete and specific ways, such as helped them to learn to monitor their condition, set goals, and/or set up and exercise program, were more activated than patients who said their provider did not help them in The predicted probabilities are computed based upon full regression models presented in online appendix 2 these ways 36,37 . While not formally evaluated, some patientcentered medical homes are measuring their patients' activation levels, and using it as a "vital sign" to help them tailor patient care plans to the patient's ability to follow through on those plans.…”
Section: A Focus On Tailoring Support To the Individual's Level Of Acmentioning
confidence: 99%
“…For example, there is evidence from cross-sectional studies that provider behaviors can support patient activation. Patients who report that their provider helped them in very concrete and specific ways, such as helped them to learn to monitor their condition, set goals, and/or set up and exercise program, were more activated than patients who said their provider did not help them in The predicted probabilities are computed based upon full regression models presented in online appendix 2 these ways 36,37 . While not formally evaluated, some patientcentered medical homes are measuring their patients' activation levels, and using it as a "vital sign" to help them tailor patient care plans to the patient's ability to follow through on those plans.…”
Section: A Focus On Tailoring Support To the Individual's Level Of Acmentioning
confidence: 99%
“…Evidence-based communication strategies such as collaborative goal setting, action planning, motivational interviewing, shared decision making, cognitive behavioral therapy, problem solving, selfefficacy enhancement, teach-back, and relapse-prevention strategies are also effective (120,(136)(137)(138)(139). It is crucial to develop action-oriented behavior change goals and objectives (130,140).…”
Section: Standard 7 Individualizationmentioning
confidence: 99%
“…6 Physician skills such as participatory decision making can lead to improved patient activation and better outcomes. 7 Hibbard's Patient Activation Measure (PAM) has been shown to be a reliable measure, relatively easy to administer, and has been proposed as a health care quality measure. [8][9][10] While more definitive study is needed, we have shown that measures of patient activating skills of residents in an Objective Structured Clinical Examination (OSCE) can identify residents more likely to promote actual weight loss in obese patients.…”
Section: Introductionmentioning
confidence: 99%